Pengaruh Kecerdasan Emosional dan Kompetensi Kepribadian Guru terhadap Prestasi Belajar Siswa Madrasah Aliyah di Pondok Pesantren Qotrun Nada Depok - Nani Prihatini; Amie Primarni; Nanat Fatah Natsir (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2019)
The purpose of this research is to examine the influence of the teacher's emotional intelligence to the students ' learning achievements, there is no influence of the teacher's personality competence on student learning achievements, and there is no influence on the emotional intelligence and personality competence of the teacher simultaneously on student learning achievement. The method used in this study is quantitative. With the number of respondents 154 students Madrasah Aliyah Qotrun Nada Depok. The approach used is multiple linear regression, consisting of two free variables, i.e. emotional intelligence and teacher personality competence. The variables are students ' learning achievements. From the results of research obtained, that there is the influence of the teacher's emotional intelligence to the learning achievement students of Madrasah Aliyah Qotrun Nada. It is evidenced by the test value T, the value of sig 0.001 < 0.05 then Ho rejected and Ha accepted. There is the influence of teacher personality competence on learning achievement of Madrasah Aliyah Qotrun Nada. It is evidenced by the test value T, the value of sig 0.000 < 0.05 then Ho rejected and Ha accepted. The emotional intelligence and personality competence of the teacher contributed concurrently to the learning achievement as much as 35.5%, it is evidenced by the test F.